First Report of Tobacco Streak Virus Infecting Sunflower in Argentina - Cabrera Mederos, Dariel; Trucco, Veronica Milagros; Bejerman, Nicolas Esteban; Lenardon, Sergio Luis; Giolitti, Fabian (American Phytopathological Society, 2020)
Sunflower (Helianthus annuus) is one of the main oleaginous crops in the world, and Argentina is positioned among the top sunflower seed producers worldwide (FAO 2019). During the 2018 to 2019 crop season, sunflower plants showing symptoms similar to those reported for the tobacco streak virus (TSV) were observed in one field of Rivera, Buenos Aires province. The symptoms included leaf mosaic and severe necrosis of stem, petioles, leaves, and pith, often progressing to complete collapse and death of affected plants. Samples from symptomatic leaf tissue were collected from five plants, and leaves of sunflower seedlings maintained under greenhouse conditions were used as the healthy control. Leaf extracts obtained from symptomatic leaves were positive by double antibody sandwich ELISA test, using a polyclonal antibody against TSV (Bioreba, Reinach, Switzerland). The average optical density of infected samples was 0.384, eight times higher than the mean plus three standard deviations of four healthy controls. Total RNA was extracted from collected samples using an RNeasy Plant Mini Kit (Qiagen, Hilden, Germany) and tested by reverse transcription polymerase chain reaction (RT-PCR) with specific TSV primers (Almeida et al. 2005). Only infected samples produced expected amplicons (∼1 kb). The RT-PCR products obtained in duplicate from two symptomatic plants were purified and sequenced in both directions